Estudo da lesão renal aguda em pacientes submetidos a transplante de células tronco hematopoiéticas no Hospital Universitário Walter Cantídio - Duarte, Pastora Maria Araujo (2021)
Introduction: Hematopoietic stem cell transplantation (HSCT) is a procedure widely performed in patients with hematological, malignant or not, autoimmune diseases and metabolic disorders, with an increase in overall survival. Despite this, acute kidney injury remains a frequent complication, affecting 10-70% of patients, contributing to an expressive mortality. Objectives: Analyze the occurrence of Acute Kidney Injury (AKI) in patients undergoing hematopoietic stem cell transplantation. Correlate the sociodemographic and clinical profile and variables related to HSCT with the onset and evolution of AKI, in addition to the impact on overall and event-free survival. Material and Methods: Retrospective cohort study, with descriptive and analytical approach, including all patients undergoing HSCT between jan/2014 and dec/2019 at Hospital Universitário Walter Cantídio (HUWC). Patients with chronic kidney disease on dialysis were excluded. Data were collected from multidisciplinary medical records and Master platform for laboratory tests and were tabulated in Microsoft Excel® 2016. The analysis was performed using software R version 4.0.3, adopting a confidence level of 95%. For identification and stratification of AKI, the KDIGO method was used. The association of variables with the presence of AKI was performed using the Chi-square test or Fisher's exact test 2x2. Normality test used was Shapiro Wilk. For quantitative or ordinal variables, Student's t test or Mann-Whitney test was considered when data were not normal. Serum creatinine was used as a marker of glomerular filtration rate (GFR) at time Zero, d0--30, d31-60 and d61-100 after HSCT. We used the CKD-EPI formula for estimation and the comparison of the four measures was made by the ANOVA test or Friedman test. Analysis of the impact of AKI on survival was performed using the Kaplan-Meyer survival curve and the log rank test. Results: 391 patients were included in the analysis, who were predominantly men (54.99%), with a median age of 47 years, mostly from the public network (57.29%). The most prevalent underlying disease was multiple myeloma (35.04%), followed by lynphoma (28,38%). We had 264 autologous (67.52%) and 127 halogen (32.48%) HSCT. AKI was diagnosed in 129 patients (32.99%). The majority of patients (53.48%) were classified as stage 1 in the KDIGO system. The non-oliguric form predominated (84.49%), with an average installation time of 32 days after HSCT and an average 8 recovery time of 35 days. Thirteen patients (10.07%) used renal replacement therapy (RRT). Seventy-three patients (56.58%) recovered their kidney function, while twentytwo (17.05%) died and fifteen (11.62%) progressed to chronic kidney disease. In bivariate analysis, the variables independently associated with AKI were: Halogen transplantation (RR 4.31 95%CI p<0.001), diagnosis of leukemia (RR 2,85 95% CI p<0.001), need for transfusion of packed red blood cells ( RR 2.2 95% CI p<0.001) , use of three or more classes of antimicrobials (RR 2.1 95% CI p <0.001), use of amphotericin B (RR 3.08 CI 95% p<0.001), polymyxin B (RR 2.4 CI 95% p<0.001), amikacin (RR 2.51 CI 95% p 0.040), voriconazole (RR 2.15 95% CI p<0.001), engraftment time (p<0.001), BuFlu conditioning protocols (RR 2.98 95% CI p<0.001 ), CyATG (RR 3.08 95% CI p 0.035), FluCyATG (RR 2.02 95% CI p 0.018), FluMel 140 (RR 2.34 95% CI p 0.018) and FluMel180 (RR 1.93 CI 95 % p 0.006) , sepsis/septic shock (RR 1.99 CI 95% p<0.001) , sinusoidal obstruction syndrome (RR 3.17 CI 95% p 0.003) , cytomegalovirus infection (R R 2.18 95% CI p<0.001), grade III mucositis (RR 2.42 95% CI p<0.001) and use of calcineurin inhibitors (p<0.001). The test post hoc showed that basal and early creatinines were different and higher than intermediate and late (p<0.001) and that GFR in patients with AKI were lower than in those without AKI in all periods, except for baseline (p<0.001). The survival time of the group without AKI was higher than the group with AKI (p<0.001), and in these groups, the need to use renal replacement therapy (RRT) determined a higher risk of death (p<0.001). Among those who underwent conservative treatment, we found greater survival in those who recovered their kidney function. Conclusion: The incidence of AKI in patients undergoing HSCT at the HUWC was high, with classical association variables confirming its importance and impact on patient survival.